Monitoring In-Situ Seismic Response on Rock Slopes Using Ambient Noise Interferometry: Application to the 2019 Changning (Mw 5.7) Earthquake, China - Huang, Huibao; Dai, Shigui; Xie, Fan (Frontiers in Earth Science, 2021)
Study of the mechanical response of rock slopes to moderate earthquakes is important for understanding the local rheology of landslide and earthquake interactions and for mitigating the risks associated with subsurface geological processes in tectonically active mountainous belts. To complement existing point measurements from surface observations (e.g., global positioning system and interferometric synthetic-aperture radar measurements), measuring the ambient noise-based velocity change (δv/v) allows for remote observations of mechanical state changes of the slope, at depth and continuously in time. We herein investigate the seismic responses of the Pubugou rock slope, a typical steep rock slope in south-west China, to the 2019 Mw 5.7 Changning earthquake. We apply ambient noise interferometry to the slope and measure the coda wave velocity changes at frequencies from 2 to 20 Hz with a 1-h temporal resolution, 2 days before and 14 days after the earthquake. We observe a significant co-seismic wave velocity decrease caused by the Changning earthquake of up to 0.9% followed by a gradual logarithmic recovery process over 2 weeks. The earthquake-induced stress sensitivity of δv/v on the slope is estimated as ∼3.2×10−8 Pa−1. Through the analysis of the co-seismic and post-seismic δv/v with different time lapses of the coda, we characterize the healing process on the slope and also constrain such changes to 75 m in depth. This study highlights the possibility of quantitatively characterizing the slope weakness using moderate earthquakes in mountainous areas in the future.